Single-Stage Resource Allocation and Economic Lot Scheduling on Multiple, Nonidentical Production Lines - Bollapragada, Ramesh; Rao, Uday (Management Science, 1999)
This paper focuses on simultaneous resource allocation, lot-sizing, and scheduling in a multimachine, deterministic ELSP environment. We consider the problem of apportioning item production to distinct manufacturing lines with different costs and capabilities (production rates). The objective is to minimize the long-run average production, setup, inventory, and shortage penalty costs (due to lost sales). Restricting attention to rotation schedules, we develop a concave minimization model of the problem, generate heuristic solutions and a lower bound on the cost of any feasible solution. Computational experiments indicate that our heuristic solution is within a few percent of the lower bound. We also investigate sensitivity of costs to model parameters, and illustrate how our model may be used to determine target values for equipment utilization.